Designing the Powertrain of Unmanned Aerial Vehicle to Carry a 40 Kg Payload at Kabale University. - Nalumansi Moureen (Kabale University, 2023)
The project is about designing the powertrain of an unmanned aerial vehicle (UAV) to carry payload of 40kg payload. This UAV powertrain is a photovoltaic and battery powered system designed for agricultural application. This is achieved by estimating the total weight and required power of the UAV, designing the motor and propeller unit parameters, and sizing the solar and battery system. The powertrain is designed with four brushless DC motor and carbon fiber propellers because of their later on mentioned advantages and monocrystalline solar modules and lithium-ion batteries are considered. Keywords; Powertrain, Unmanned Aerial Vehicle, Photovoltaic, Brushless DC motors, Payload and Lithium-ion batteries.